BurnCase 3D software validation study: Burn size measurement accuracy and inter-rater reliability. Issue 2 (March 2016) - Parvizi, Daryousch; Giretzlehner, Michael; Wurzer, Paul; Klein, Limor Dinur; Shoham, Yaron; Bohanon, Fredrick J.; Haller, Herbert L.; Tuca, Alexandru; Branski, Ludwik K.; Lumenta, David B.; Herndon, David N.; Kamolz, Lars-P.
Abstract: Objective: The aim of this study was to compare the accuracy of burn size estimation using the computer-assisted software BurnCase 3D (RISC Software GmbH, Hagenberg, Austria) with that using a 2D scan, considered to be the actual burn size. Methods: Thirty artificial burn areas were pre planned and prepared on three mannequins (one child, one female, and one male). Five trained physicians (raters) were asked to assess the size of all wound areas using BurnCase 3D software. The results were then compared with the real wound areas, as determined by 2D planimetry imaging. To examine inter-rater reliability, we performed an intraclass correlation analysis with a 95% confidence interval. Results: The mean wound area estimations of the five raters using BurnCase 3D were in total 20.7 ± 0.9% for the child, 27.2 ± 1.5% for the female and 16.5 ± 0.1% for the male mannequin. Our analysis showed relative overestimations of 0.4%, 2.8% and 1.5% for the child, female and male mannequins respectively, compared to the 2D scan. The intraclass correlation between the single raters for mean percentage of the artificial burn areas was 98.6%. There was also a high intraclass correlation between the single raters and the 2D Scan visible. Conclusion: BurnCase 3D is a valid and reliable tool for the determination of total body surface area burned in standard models. Further clinical studies including different pediatric and overweight adult mannequins are warranted.